Efektivitas Penerapan Aplikasi Zoom Dengan Menggunakan Metode TAM (Studi Kasus : SMP NEGERI 1 PPU) - Wahyuni, Sri; Surmiati; Adi Hermawansyah (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study aims to determine the effectiveness of the application of the Zoom application used by teachers and students at SMP NEGERI 1 PPU. The framework used is the Technology Acceptance Model which has 5 main constructions, namely 1) Benefits in using the application 2) Ease of using the application 3) Attitude in using the application 4) Intention to use the application 5) The actual use of the application. The research method used is a quantitative method with a case study approach which is carried out throughdistributing questionnaires containing 16 questions each and then given to respondents. The data obtained from the respondents were then processed using SPSS (Statistical Product and Service Solution) software. Respondents used were 23 teachers and 84 students of SMP NEGERI 1 PPU whose number was determined using cluster random sampling technique so that the number of respondents became more accurate. Before distributing the questionnaire, the researcher first used several samples to determine whether the questionnaire was valid or not. The results showed that the use of the Zoom Meeting application was able to have a positive impact on its users, namely teachers and students in terms of perceived usefulness, perceived ease of use, attitude toward using, intention to use and good use. actually (Actual Use). The researcher first used several samples to determine whether the questionnaire was valid or not. The results showed that the use of the Zoom Meeting application was able to have a positive impact on its users, namely teachers and students in terms of perceived usefulness, perceived ease of use, attitude toward using, intention to use and good use. actually (Actual Use). The researcher first used several samples to determine whether the questionnaire was valid or not. The results showed that the use of the Zoom Meeting application was able to have a positive impact on its users, namely teachers and students in terms of perceived usefulness, perceived ease of use, attitude toward using, intention to use andgood use. actually (Actual Use).